Current aspects on the selection of patients who are candidates for lung transplantation (Research, Society and Development, 2023)
Currently, the main indications for lung transplantation worldwide are chronic obstructive pulmonary disease (COPD), pulmonary fibrosis, cystic fibrosis, alpha-1-antitrypsin (alpha-1) deficiency, idiopathic pulmonary arterial hypertension, bronchiectasis, retransplantation, sarcoidosis and severe lung injury caused by COVID-19, and these candidates must demonstrate knowledge regarding the procedure, good adherence to the medical treatment performed, adequate psychosocial structure and family support. Furthermore, the proper assessment of contraindications contributes to a lower occurrence of unfavorable clinical outcomes unrelated to the graft, benefiting patients with a greater chance of success and, thus, improving overall survival with treatment. Among the absolute contraindications, lung cancer, cardiac dysfunction unrelated to lung disease, significant organic dysfunction of any other noble organ, hepatitis B and C virus infections, active pulmonary tuberculosis and severe rib cage deformity stand out. Furthermore, among the relative contraindications, there is age over 65 years, severe clinical instability, HIV infection, obesity, severe osteoporosis and decompensated systemic diseases.